Effects of sevoflurane and desflurane on early cognitive changes after thyroid surgery: interim results - Kuzminskaitė, Vilma; Slauzgalvytė, Ieva; Bukelytė, Greta; Bruzytė, Greta; Kontrimavičiūtė, Eglė (Acta medica Lituanica, 2019)
The study is being conducted at the 1st Department of Anaesthesiology, the Centre of Abdominal Surgery, the Centre of Anaesthesiology, Intensive Care and Pain Management of Vilnius University Hospital Santaros Klinikos. Background. These are primary results of a randomized double-blinded study comparing postoperative changes in cognitive functions and the effect of desflurane and sevoflurane on these changes. Materials and methods. The study includes patients of ≥40 years of age undergoing elective thyroid surgery under general anaesthesia. Patients were randomly allocated to either sevoflurane or desflurane group. Cognitive testing (memory, attention, and reasoning tasks) was performed a day before surgery and repeated 24 hours postoperatively. A decrease of 20% in the postoperative score was considered as postoperative cognitive dysfunction (POCD). Results. At present 38 patients are included in the study. Median decrease in the postoperative score was 2.7% (IQR 16.7). The incidence of POCD was 2.6%. Significantly decreased memory scores were observed in 15.8% of patients. Both study groups were comparable based on demography, duration of anaesthesia, intraoperative opioids, postoperative pain, and satisfaction. No difference was found in the cognitive score comparing sevoflurane and desflurane groups, except for memory tasks where the sevoflurane group performed worse (p = 0.01). The age or the duration of anaesthesia did not affect postoperative scores. Postoperative satisfaction negatively correlated with the memory score (r = –0.35, p = 0.03). Postoperative satisfaction correlated with the reasoning score (r = –0.55; p < 0.01) and the total score (r = –0.42; p = 0.03) in the sevoflurane group. Likewise, temperature in the sevoflurane group correlated with the memory score (r = –0.58; p = 0.02). Conclusions. The desflurane group performs better in memory tasks, but no such advantage is found in the total cognitive score. In contrast to the age or anaesthesia duration, intraoperative temperature and postoperative satisfaction may affect postoperative cognitive performance.
Keywords: cognitive disorders; sevoflurane; desflurane; POCD